Imaging of SARS-CoV-2 infected Vero E6 cells by helium ion microscopy - Frese, Natalie; Schmerer, Patrick; Wortmann, Martin; Schürmann, Matthias; König, Matthias; Westphal, Michael; Weber, Friedemann; Sudhoff, Holger; Gölzhäuser, Armin (Beilstein Journal of Nanotechnology, 2021)
Helium ion microscopy (HIM) offers the opportunity to obtain direct views of biological samples such as cellular structures, virus particles, and microbial interactions. Imaging with the HIM combines sub-nanometer resolution, large depth of field, and high surface sensitivity. Due to its charge compensation capability, the HIM can image insulating biological samples without additional conductive coatings. Here, we present an exploratory HIM study of SARS-CoV-2 infected Vero E6 cells, in which several areas of interaction between cells and virus particles, as well as among virus particles, were imaged. The HIM pictures show the three-dimensional appearance of SARS-CoV-2 and the surface of Vero E6 cells at a multiplicity of infection of approximately 1 with great morphological detail. The absence of a conductive coating allows for a distinction between virus particles bound to the cell membrane and virus particles lying on top of the membrane. After prolonged imaging, it was found that ion-induced deposition of hydrocarbons from the vacuum renders the sample sufficiently conductive to allow for imaging even without charge compensation. The presented images demonstrate the potential of the HIM in bioimaging, especially for the imaging of interactions between viruses and their host organisms.
Keywords: bioimaging; cell membrane; charge compensation; helium ion microscopy; SARS-CoV-2; Vero E6 cells

Helium Ion Microscopy - Hlawacek, G.; Gölzhäuser, A. (Springer International Publishing, 2016)

(untitled) - Vanden Berg-Foels, W. S.; Scipioni, L.; Huynh, C.; Wen, X. (J. Microsc. (Oxford, U. K.), 2012)

(untitled) - BAZOU, D.; BEHAN, G.; REID, C.; BOLAND, J. J.; ZHANG, H. Z. (J. Microsc. (Oxford, U. K.), 2011)

(untitled) - Chen, X.; Udalagama, C. N. B.; Chen, C.-B.; Bettiol, A. A.; Pickard, D. S.; Venkatesan, T.; Watt, F. (Biophys. J., 2011)

(untitled) - Rice, W. L.; Van Hoek, A. N.; Păunescu, T. G.; Huynh, C.; Goetze, B.; Singh, B.; Scipioni, L.; Stern, L. A.; Brown, D. (PLoS One, 2013)

(untitled) - Schürmann, M.; Frese, N.; Beyer, A.; Heimann, P.; Widera, D.; Mönkemöller, V.; Huser, T.; Kaltschmidt, B.; Kaltschmidt, C.; Gölzhäuser, A. (Small, 2015)

(untitled) - Greiner, J. F. W.; Hauser, S.; Widera, D.; Müller, J.; Qunneis, F.; Zander, C.; Martin, I.; Mallah, J.; Schuetzmann, D.; Prante, C.; Schwarze, H.; Prohaska, W.; et al. (Eur. Cells Mater., 2011)

(untitled) - Leppänen, M.; Sundberg, L.-R.; Laanto, E.; de Freitas Almeida, G. M.; Papponen, P.; Maasilta, I. J. (Adv. Biosyst., 2017)

(untitled) - Said, N.; Chatzinotas, A.; Schmidt, M. (Adv. Biosyst., 2019)

(untitled) - Chen, S.-C.; Musat, N.; Lechtenfeld, O. J.; Paschke, H.; Schmidt, M.; Said, N.; Popp, D.; Calabrese, F.; Stryhanyuk, H.; Jaekel, U.; Zhu, Y.-G.; Joye, S. B.; et al. (Nature, 2019)

(untitled) - Schmidt, M.; Byrne, J. M.; Maasilta, I. J. (Beilstein J. Nanotechnol., 2021)

(untitled) - Corman, V. M.; Lienau, J.; Witzenrath, M. (Internist, 2019)

(untitled) - Wu, F.; Zhao, S.; Yu, B.; Chen, Y.-M.; Wang, W.; Song, Z.-G.; Hu, Y.; Tao, Z.-W.; Tian, J.-H.; Pei, Y.-Y.; Yuan, M.-L.; Zhang, Y.-L.; et al. (Nature, 2020)

Coronavirus COVID-19 Dashboard, Johns Hopkins University

(untitled) - Takayama, K. (Trends Pharmacol. Sci., 2020)

(untitled) - Zhu, N.; Zhang, D.; Wang, W.; Li, X.; Yang, B.; Song, J.; Zhao, X.; Huang, B.; Shi, W.; Lu, R.; Niu, P.; Zhan, F.; et al. (N. Engl. J. Med., 2020)

(untitled) - Algarroba, G. N.; Rekawek, P.; Vahanian, S. A.; Khullar, P.; Palaia, T.; Peltier, M. R.; Chavez, M. R.; Vintzileos, A. M. (Am. J. Obstet. Gynecol., 2020)

(untitled) - Harcourt, J.; Tamin, A.; Lu, X.; Kamili, S.; Sakthivel, S. K.; Murray, J.; Queen, K.; Tao, Y.; Paden, C. R.; Zhang, J.; Li, Y.; Uehara, A.; et al. (Emerging Infect. Dis., 2020)

(untitled) - Bouhaddou, M.; Memon, D.; Meyer, B.; White, K. M.; Rezelj, V. V.; Correa Marrero, M.; Polacco, B. J.; Melnyk, J. E.; Ulferts, S.; Kaake, R. M.; Batra, J.; Richards, A. L.; et al. (Cell, 2020)

(untitled) - Prasad, S.; Potdar, V.; Cherian, S.; Abraham, P.; Basu, A.; ICMR-NIV NIC Team (Indian J. Med. Res., 2020)

(untitled) - Wolff, G.; Limpens, R. W. A. L.; Zevenhoven-Dobbe, J. C.; Laugks, U.; Zheng, S.; de Jong, A. W. M.; Koning, R. I.; Agard, D. A.; Grünewald, K.; Koster, A. J.; Snijder, E. J.; Bárcena, M. (Science, 2020)

(untitled) - Ward, B. W.; Notte, J. A.; Economou, N. P. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 2006)

(untitled) - Hlawacek, G.; Veligura, V.; van Gastel, R.; Poelsema, B. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2014)

“New Images of Novel Coronavirus SARS-CoV-2 Now Available”, NIAID Media Team, Feb 17, 2020, USA

(untitled) - Joens, M. S.; Huynh, C.; Kasuboski, J. M.; Ferranti, D.; Sigal, Y. J.; Zeitvogel, F.; Obst, M.; Burkhardt, C. J.; Curran, K. P.; Chalasani, S. H.; Stern, L. A.; Goetze, B.; et al. (Sci. Rep., 2013)

(untitled) - Rothe, C.; Schunk, M.; Sothmann, P.; Bretzel, G.; Froeschl, G.; Wallrauch, C.; Zimmer, T.; Thiel, V.; Janke, C.; Guggemos, W.; Seilmaier, M.; Drosten, C.; et al. (N. Engl. J. Med., 2020)

(untitled) - Felgenhauer, U.; Schoen, A.; Gad, H. H.; Hartmann, R.; Schaubmar, A. R.; Failing, K.; Drosten, C.; Weber, F. (J. Biol. Chem., 2020)

(untitled) - Bojkova, D.; Klann, K.; Koch, B.; Widera, M.; Krause, D.; Ciesek, S.; Cinatl, J.; Münch, C. (Nature, 2020)

(untitled) - Cohen-Tanugi, D.; Yao, N. (J. Appl. Phys., 2008)

(untitled) - Bell, D. C. (Microsc. Microanal., 2009)

(untitled) - Ennos, A. E. (Br. J. Appl. Phys., 1953)

(untitled) - Isaacson, M. (Ultramicroscopy, 1979)

(untitled) - Hren, J. J. (Ultramicroscopy, 1978)

(untitled) - van Gastel, R.; Barriss, L.; Sanford, C.; Hlawacek, G.; Scipioni, L.; Merkle, A. P.; Voci, D.; Fenner, C.; Zandvliet, H. J. W.; Poelsema, B. (Microsc. Microanal., 2011)

(untitled) - Hlawacek, G.; Veligura, V.; Lorbek, S.; Mocking, T. F.; George, A.; van Gastel, R.; Zandvliet, H. J. W.; Poelsema, B. (Beilstein J. Nanotechnol., 2012)

(untitled) - Veligura, V.; Hlawacek, G.; van Gastel, R.; Zandvliet, H. J. W.; Poelsema, B. (Beilstein J. Nanotechnol., 2012)

(untitled) - Wirtz, T.; De Castro, O.; Audinot, J.-N.; Philipp, P. (Annu. Rev. Anal. Chem., 2019)

(untitled) - Wang, S.-M.; Huang, K.-J.; Wang, C.-T. (Virology, 2014)

(untitled) - Caldas, L. A.; Carneiro, F. A.; Higa, L. M.; Monteiro, F. L.; da Silva, G. P.; da Costa, L. J.; Durigon, E. L.; Tanuri, A.; de Souza, W. (Sci. Rep., 2020)

(untitled) - Mahauad‐Fernandez, W. D.; Okeoma, C. M. (Immun., Inflammation Dis., 2016)

(untitled) - Berry, K. N.; Kober, D. L.; Su, A.; Brett, T. J. (BioEssays, 2018)

(untitled) - Hammonds, J.; Wang, J.-J.; Yi, H.; Spearman, P. (PLoS Pathog., 2010)